Left atrial appendage occlusion. Issue 11 (17th December 2014) - Alli, Oluseun; Holmes, David
Abstract : Left atrial appendage (LAA) occlusion for stroke and thromboembolism prevention in patients with atrial fibrillation (AF) represents a significant advancement in the field of cardiovascular disease. Prevention and avoidance of the devastating consequences of thromboembolic complications from AF continues to be central in the management of these patients. The role of LAA as a nidus for thrombus formation is well documented. Multiple approaches to exclude the LAA from the circulation either percutaneously or surgically have been described and are undergoing testing. Although pharmacological therapy for stroke prevention remains the cornerstone of treatment, device and surgical exclusion of the LAA have proven to be viable alternatives in carefully selected patients. Even though current evidence show that LAA occlusion is safe and effective, approval and adoption of this strategy has been quite difficult due to paucity of randomised clinical trial data on the risk and benefit ratio, cost effectiveness and the issues of procedural risk as well as longer-term outcome. This review aims to provide an update on the current status of LAA occlusion, specifically looking at interpretation of current clinical data, available techniques and devices, issues with current devices and future direction.